2022
DOI: 10.1109/tvcg.2020.3035823
|View full text |Cite
|
Sign up to set email alerts
|

Rainbow Dash: Intuitiveness, Interpretability and Memorability of the Rainbow Color Scheme in Visualization

Abstract: Figure 1. Tested color schemes (top row) and responses to T1: order hues (in columns below). Each row shows a unique sequence provided by at least one participant (counts are shown next to each set). Participants ordered the colors from "min to max" (left to right) purely based on their perceptual associations for the seven hues. We see 101 different orders for the rainbow and seven for the sequential schemes. The 'correct' sets are shown on top.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…• OMC ∼ Viridis ∼ Rainbow OMC sl ColorCrafter In general, our study results confirm findings from Golebiowska and Coltekin [6] that multi-colored scales like OMC and Rainbow are more suitable for reading tasks while sequential scales like Viridis work better for comparing tasks.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…• OMC ∼ Viridis ∼ Rainbow OMC sl ColorCrafter In general, our study results confirm findings from Golebiowska and Coltekin [6] that multi-colored scales like OMC and Rainbow are more suitable for reading tasks while sequential scales like Viridis work better for comparing tasks.…”
Section: Discussionsupporting
confidence: 88%
“…Color Perception Golebiowska and Coltekin [6] explored the perceptual differences from rainbow to sequential color scales. Their study showed that the sequential colormaps performed better in comparing values and recognizing general patterns, whereas the rainbow scale supports the reading of specific details.…”
Section: Related Workmentioning
confidence: 99%
“…Future research efforts might also investigate ways in which to include contextual factors of the map use environment, which we have not included in this study but are part of the context model by Griffin et al [5]. Since we measured the task success rates, comfort, and confidence ratings, it would also be interesting to include evaluation metrics such as learnability, memorability of spatial information, or decision-making accuracy [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, heat maps have rarely been used as study material in empirical cartographic user-centered research. Map types with smooth presentation of data are often the subject of color scheme studies [34][35][36][37]. So far, in terms of the usability of heat maps, only studies of the subjective metrics and scenario-based design methods have been conducted.…”
Section: Heat Maps and Generalization In Cartographymentioning
confidence: 99%